CTNI-26. SURGICAL WINDOW OF OPPORTUNITY TRIAL OF NAVTEMADLIN (KRT 232; AMG232) IN PATIENTS WITH RECURRENT GLIOBLASTOMA. (14th November 2022) - Lee, Eudocia; Rudek, Michelle; Rendo, Veronica; Khuu, Nicholas; Walbert, Tobias; Holdhoff, Matthias; Lieberman, Frank; Desai, Arati; Strowd, Roy; Lapinskas, Emily; Pelton, Kristine; Pisano, William; et al.
Abstract: BACKGROUND: KRT232 is an orally bioavailable, selective small molecule inhibitor of MDM2 that blocks the protein-protein interaction between MDM2 and p53. We performed a surgical window of opportunity trial of KRT232 in patients with recurrent GBM. METHODS: The primary endpoint was to determine the tumor tissue concentration of KRT232. Prior to surgery, patients received KRT232 at either 120mg (n = 10, minimal dose that is consistently associated with alterations in serum MIC-1) or 240mg (n = 10; recommended phase 2 dose as monotherapy) for two days prior to surgical resection. Surgery was performed 3-6 hours following the last administration of KRT232. Tissue was analyzed for KRT232 concentration by LC/MS and for correlative studies. Participants with TP53 wild-type tumors were eligible to continue KRT232 following recovery from surgery at the RP2D of 240mg QD x 7 days q3weeks. RESULTS: Twenty-one patients were enrolled from July 2018 to April 2020. One patient was deemed ineligible after surgery due to non-GBM tumor. Study met the prespecified criteria of target intra-tumor drug concentration of ≥ 25nM in contrast enhancing tissue in more than 50% of the patients in the 120mg cohort (67.1 ± 42.7nM in 8/10 patients) and 240mg (328.7 ± 468.1nM in 10/10 patients) cohort. Serum MIC-1 fold-changes from baseline (FCB) approximately 24 hours after a single dose of KRT232 were higher in the 240mg cohort (9.1 ± 4.1-FCB) than the 120mg cohort (3.6 ± 2.0-FCB). CDKN1A (p21), a downstream marker of p53, was significantly upregulated in analyzed participants whose GBM was TP53 wildtype, but not in TP53 mutant GBM or control samples (GBM treated with standard of care). CONCLUSION: KRT232 at both 120mg and 240mg achieves adequate tumor tissue penetration and affects downstream pathways in TP53 wildtype GBM. The study has moved to Alliance to complete a phase 1 study of radiation + KRT232 in patients with newly diagnosed MGMT unmethylated GBM.